A relação dialógica como pressuposto no processo avaliativo: um estudo sobre as marcas linguísticas e a construção de inferências - Silva, Débora Maria dos Santos Castro (2010)
This dissertação investigates the way for which the citizens construct (s) the sensible one (s) in the avaliativo context and as this if it reflects in its productions written in classroom. The corpus analyzed in this work is constituted by written texts produced for pupils of as the module of the course of Secretaryship of the Federal Institute of Education, Science and Technology of the Tocantins - Campus Palms in reply the referring avaliativas questions the two curricular components of the course (Introduction to the Marketing and Right, Legislation and Ethics) and also for the answers given for pupils and its professors to the carried through interview. We leave of the estimated one of that the interpretation of the avaliativas questions depends in such a way on the procedures of decoding as of the accomplishment of inferences, therefore we very believe to be difficult to have understanding without inferences. Having this in mind, we search to investigate of that way the elaboration of the avaliativas questions can intervene with the inferencial performance of the pupils; of that it forms the conception of evaluation of the pupils exerts influence in the inferenciais processes. Moreover, we search to relate the linguísticas marks gifts in the avaliativas questions and the inferences had in the commentaries of the citizens. For the enterprise of our research we opt to adopting the sociocognitivointeracionista conception of reading according to which the direction does not exist a priori, being a construction that involves the interaction author-text-reader. E, in the special case of the evaluations used in our research, we perceive that the inferences produced for the pupils are regulated not only by the vision decoder of the evaluation defended for the searched professors, but also for the traditional conception of evaluation of the learning.